KEANEKARAGAMAN DALAM KESATUAN HUKUM: MODEL INTERAKSI HUKUM ADAT DAN HUKUM NEGARA DALAM HUKUM AGRARIA (STUDI KASUS DI SUMATERA BARAT) - KURNIA WARMAN (Jurnal Media Hukum, 2012)
The regulation on agrarian resources can not be separated from adat law since they are located in the area where adat community lives. The lowest is their regulation by the state law, the greatest is the possibility for the adat law to fill in the substance of the regulation. The decentralization policy has opened the possibility for the local people to actualize the local adat law values through the legal products in the local area. This research studies the implementation of the actualization of the local values in the agrarian regulation in West Sumatra which is one of the areas which has a relatively strong adat law. Beside the implementation of adat law through the judicial process, this research is also focused on the integration between adat law and state law through the local legal products from the province level until the nagari (village) level. Based on the above considerations, the objective of the research is focused on three problems. They are: the first, how is the interaction between adat law and state law in the regulation of agrarian resources in West Sumatra before the era of decentralization? The second, how is the interaction between adat law and state law in the regulation of agrarian resources in West Sumatra in the era of decentralization, especially in the implementation of the system of nagari government? The third, how is the form of the integration between adat law and state law in pursuing the real legal certainty in agrarian sector?